1996
DOI: 10.1002/bbpc.19961001112
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory: Structure and interfacial properties of binary mixtures

Abstract: Based on Density Functional Theory (DFT) of inhomogeneous fluid mixtures we model the liquid-vapour interface of some binary mixtures. Attractive contributions to the Helmholtz free energy are treated by a mean-field approximation (MF). The local density approximation (LDA) is applied to the repulsive reference system described by a hard sphere equation of state. A cut-off and shifted Lennard-Jones-12-6 potential divided according to the WCA-prescription is used as interaction pair potential. Binary Lennard-Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…In order to specify a physically value the 10/90-rule, given by Lekner and Henderson [29] can be used. The second quantity that can be calculated is the adsorption isotherms with the help of the concepts given by Telo da Gama and Evans [30,31] and Wadewitz and Winkelmann [32] we can describe the symmetrized interface segregation C(z):…”
Section: Binary Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to specify a physically value the 10/90-rule, given by Lekner and Henderson [29] can be used. The second quantity that can be calculated is the adsorption isotherms with the help of the concepts given by Telo da Gama and Evans [30,31] and Wadewitz and Winkelmann [32] we can describe the symmetrized interface segregation C(z):…”
Section: Binary Mixturesmentioning
confidence: 99%
“…Once the symmetrized interface segregation is calculated the relative adsorption can also be defined as [32]:…”
Section: Binary Mixturesmentioning
confidence: 99%
“…The present paper is part of a systematic investigation on density functional theory of simple liquids and their mixtures [22][23][24][25] and on molecular dynamics simulations of vaporliquid interfaces of Lennard-Jones fluids and mixtures. 26,27 Our main interest is to compare the results of MD simulations with DFT calculations in order to evaluate the approximations made in theory.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for density functional treatments of free fluid interfaces with comparatively featureless structures, it remains commonplace to invoke the LDA, thus neglecting short-range correlations. Such studies have recently been reported not only for single-component simple fluids (26) and their binary mixtures (27), but also for molecular (28) and dipolar (29) fluids.…”
Section: Introductionmentioning
confidence: 99%